Serum ACE2 and S19P gene polymorphism in Egyptian patients with COVID-19 infection: correlation with disease severity - Gaber, Dalia A.; Shokr, Mohamed; Shaker, Olfat; Zaki, Kamelia Ahmed; Khalil, Haidy Samir; Wahb, Amany M. (Scientific reports, 2024)
The expression of ACE2 is linked to disease severity in COVID-19 patients. The ACE2 receptor gene polymorphisms are considered determinants for SARS-CoV-2 infection and its outcome. In our study, serum ACE2 and its genetic variant S19P rs73635825 polymorphism were investigated in 114 SARS-CoV-2 patients. The results were compared with 120 control subjects. ELISA technique and allele discrimination assay were used for measuring serum ACE2 and genotype analysis of ACE2 rs73635825. Our results revealed that serum ACE2 was significantly lower in SARS-CoV-2 patients ( p = 0.0001), particularly in cases with hypertension or diabetes mellitus. There was a significant difference in the genotype distributions of ACE2 rs73635825 A > G between COVID-19 patients and controls ( p -value = 0.001). A higher frequency of the heterozygous AG genotype (65.8%) was reported in COVID-19 patients. The G allele was significantly more common in COVID-19 patients ( p < 0.0001). The AG and GG genotypes were associated with COVID-19 severity as they were correlated with abnormal laboratory findings, GGO, CXR, and total severity scores with p < 0.05. Our results revealed that the ACE2 S19P gene variant is correlated with the incidence of infection and its severity, suggesting the usefulness of this work in identifying the susceptible population groups for better disease control.